Design and Analysis of Broadband High Isolation of Discrete Packaged PIN Diode SPDT Switch for Wireless Data Communication - Shairi, Noor Azwan; Ahmad, Badrul Hisham; A.C.Z., Khang (2011)
A design and analysis of broadband high isolation of discrete packaged PIN diode Single-Pole Double-Throw (SPDT) switch is presented. Many applications of wireless data communication are implementing Time Division Duplex (TDD) switching such as UMTS-TDD (in 3G technologies), LTE (in 4G technologies), HiperLAN, HiperMAN, WiFi, WiMAX and WiBRO. A broadband high isolation of SPDT switch is needed to provide these multimarket applications at different frequency bands. In this paper, three different circuit topologies (Type A, Type B and Type C) targeted for broadband high isolation are designed and analyzed. The SPDT switches are based on the discrete packaged PIN diode that available in the market for switching control. Analysis of the various configurations is done in order to select the most suitable topology for broadband high isolation SPDT switch. As results, Type C has been chosen for prototyping and measurement. In simulation and measurement, the isolation is higher than 25 dB from 0.5 to 3 GHz compared with Type A and Type B.